Electrospun Nanofiber: Application in Tissue Regeneration: Pharmaceutical Science-Pharmaceutics - Ajmal, Gufran; Yadav, Narender; Rashid Iqba, Mohammad; Mittal, Pooja (International Journal of Life Science and Pharma Research, 2022)
Abstract: An injury to the human body is classified as a wound if it results in a cut or a break in the skin. Depending on the depth of the skin layer, a wound can either be limited to the epidermal layer, which heals via re-epithelialization without the need for skin grafts, or full-thickness wounds, which result in the loss of both the epidermis and dermis (FTW). A full-thickness wound cannot heal on its own and needs a skin graft or tissue regeneration product to heal quickly. This paper provides a comprehensive overview of the properties of electrospun nanofibers and their application as skin regeneration products rapid healing of the full-thickness wound. The paper first introduces the skin, its layers, and various problems associated with human skin. In the next part, a wound is discussed in terms of acute and chronic wounds. Primary, secondary and tertiary clinical wound healing has also been discussed. The next part briefly introduces the four different phases of healing, i.e. hemostasis, inflammation, proliferative and maturation of newly deposited collagen into tissues. The effect of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) on reactive oxygen species, reactive nitrogen species and reactive sulphur species, and their effect on healing time was discussed. The electrospinning process’s evolution and setup, properties of electrospun nanofibers, a component of electrospinning solution, and various parameters affecting electrospinning were discussed. Application on nanofiber scaffold in terms of drug delivery and tissue regeneration was highlighted. In the end, improvement in the existing nanofibrous scaffold was briefly highlighted.